A Study of Energy Efficiency in Flats, Case Study: The A-B-C Tower of Tambora Flats in Jakarta, Indonesia - Eugineus Rivado Victor Laude; Satriya Wahyu Firmandhani (Journal of Architectural Design and Urbanism, 2021)
Flats are one of the government's solution to provide decent housing for low-income people. However, as mostly flats overlook energy efficiency aspects, residents must pay high rental and operational costs. Therefore, this paper aims to study the principles of green buildings, especially in the building envelope that can bear the operating costs of flats with the case study on the A-B-C Tower of Tambora Flats. The A-B-C Tower of Tambora Flats is one of the flats building in Jakarta that has rental cost issues. This study employed the EDGE application that provided energy saving values in the application of green building principles, such as building mass and orientation, wall and roof finishing materials, natural shading and ventilation elements. From these values, it was only the application of green building principles that was significant for the Tambora flats. The results of this study revealed that the optimization of natural ventilation for flats was still important and having a significant impact on energy savings